Pemberdayaan Masyarakat Melalui Penyuluhan dan Pelatihan Budidaya Tasapot dan Teknik Transplanting untuk Meningkatkan Keterampilan Ketahanan Pangan Petani di Kelompok Tani Kapasari Indah, Surabaya - Kinanti, Ceysha Berliana; Luthfiyah, Lenny; Setiawati, Beta Rianul (Unpad Press, 2025)
Extension training on potted vegetable cultivation (tasapot) and transplanting techniques is one effort to support urban farming as an agricultural solution in urban areas. This activity was carried out at the Kapasari Indah Farmers Group, Surabaya, with the aim of improving farmers' understanding and skills in potted vegetable cultivation and transplanting techniques to support food security. The method used was participatory-based extension, which included lectures, demonstrations, and hands-on practice. To measure the effectiveness of this activity, a pre-test was conducted before the extension and a post-test afterward. The results showed a significant increase in participants' understanding, with an average pre-test score of 22.73 increasing to 88.18 in the post-test, with an average difference of 65.45 points. This indicates that extension training combined with hands-on practice can improve farmers' skills in potted vegetable cultivation and transplanting techniques. Although this activity went well, there were several obstacles such as the limited duration of the extension and the limited tools and materials available to participants. Therefore, further mentoring and support for facilities are needed so that this method can be implemented sustainably in urban agriculture to support food security.